Business Strategy Analysis for Business Development on Boat Rental at PT Prima Sentosa Abadi Services in Samarinda - Salim, Umar Hi.; Puspaningkarti, Ikayanti; Welly, Welly; Pasangka, Marthinus (Jurnal Indonesia Sosial Sains, 2024)
This research aims to identify and analyze the internal and external factors faced in developing the ship rental business at PT Pelayaran Prima Sentosa Abadi Samarinda, as well as analyze and determine appropriate strategies for developing the ship rental business at PT Pelayaran Prima Sentosa Abadi in Samarinda. This research uses quantitative and qualitative methods with techniques for collecting data from primary and secondary data. Primary data was collected by interviewing informants regarding the answers to questionnaires regarding boat rental at PT Pelayaran Prima Sentosa Abadi in Samarinda, and secondary data was obtained from indirect data from informants. Internal factors in developing the ship rental business at PT Pelayaran Prima Sentosa Abadi Samarinda include strengths and weaknesses. The strength factor has a total value of 2.32, as obtained from the answers to the questionnaire. Meanwhile, the weakness factor was 0.96, which means the total internal factor value was 3.28. External factors faced in developing the ship rental business at PT Pelayaran Prima Sentosa Abadi Samarinda are opportunity and threat factors where the opportunity factor has a total value of 1.57 and the threat factor from the results of the questionnaire answers with a total value of 1.38, which means the total value of external factors is 2.95.